2015
DOI: 10.1021/acs.jafc.5b01129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Free Amino Acids, Oligopeptides, and Polypeptides on the Formation of Pyrazines in Maillard Model Systems

Abstract: Pyrazines are specific Maillard reaction compounds known to contribute to the unique aroma of many products. Most studies concerning the generation of pyrazines in the Maillard reaction have focused on amino acids, while little information is available on the impact of peptides and proteins. The present study investigated the generation of pyrazines in model systems containing whey protein, hydrolyzed whey protein, amino acids, and glucose. The impact of thermal conditions, ratio of reagents, and water activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 31 publications
1
73
0
Order By: Relevance
“…As shown by Maillard model systems, unsubstituted pyrazine was predominant in the case of free amino acids, whereas the amounts of generated alkylpyrazines were higher in the presence of peptides (Van Lancker et al, 2011). Obviously, the role of peptides in the formation of alkylpyrazines (and other flavour components) in Maillard reaction systems has been dramatically underestimated as recently reported (Scallone et al, 2015).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…As shown by Maillard model systems, unsubstituted pyrazine was predominant in the case of free amino acids, whereas the amounts of generated alkylpyrazines were higher in the presence of peptides (Van Lancker et al, 2011). Obviously, the role of peptides in the formation of alkylpyrazines (and other flavour components) in Maillard reaction systems has been dramatically underestimated as recently reported (Scallone et al, 2015).…”
Section: Discussionmentioning
confidence: 78%
“…Alkylpyrazines are not unique for roasted cocoa beans, but are widespread in the volatile fractions of roasted foods. They are generated by Maillard reactions of both free amino acids and peptides with glucose (Scallone, Cucu, De Kimpe, & De Meulenaer, 2015;Van Lancker, Adams, & De Kimpe, 2011, 2012. Older studies on the formation of pyrazines in the Maillard reaction have largely focused on free amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have found pyrazines to be more important than free amino acids in the peptide reaction system (Scalone, Cucu, De Kimpe, & De Meulenaer, ; Totlani & Peterson, ). Notably, van Lancker () reported that the production of 2,5(6)‐dimethylpyrazine and trimethylpyrazine was low in the case of Pro, Val, or Leu at the N‐terminus of X‐Lys dipeptides, whereas it was very high for Gly, Ala, or Ser.…”
Section: Resultsmentioning
confidence: 99%
“…In current studies, pyrazines, especially 2,5(6)‐dimethylpyrazine and trimethylpyrazine, constitute the most important volatile products identified in the peptide Maillard reaction system (Lu, Hao, Payne, & Ho, ; Zhang, Dorjpalam, & Ho, ). Scalone () found that the oligopeptides from hydrolyzed whey protein contributed more to pyrazine generation than free amino acids. The mechanism of pyrazine formation is widely known to occur through the condensation of α‐aminoketones formed from the interaction of α‐dicarbonyls and amines through Strecker degradation.…”
Section: Introductionmentioning
confidence: 99%